Ts. Dr. Lee Khai Loon creates specially designed chalet management system for hotel industry - Hafizatulazlin, Abdul Aziz; Nurhartini, Mohd Hatta (2021)
A lecturer from the Faculty of Industrial Management (FPI), Universiti Malaysia Pahang (UMP), Ts. Dr. Lee Khai Loon, 34, has created a research product called ChaMs.